Divorce and Financial Security: The Role of Spousal Support and Asset Division in Family Law - Shama Parveen; Suman Sarker (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study explores the financial implications of divorce, focusing on spousal support and asset division policies in family law. By analyzing case studies and legal frameworks from different countries, the research examines how equitable asset division and fair spousal support can impact financial security post-divorce. Findings suggest that well-structured financial provisions are essential for supporting financial independence and stability for individuals post-divorce.